THE STYLISTIC CHARACTERISTICS IN THE WORK OF NIKOLAI VASILYEVICH GOGOL (Slavic Studies, 2025)
This paper is a diploma thesis in which the stylistic characteristics in the works of the Russian writer Nikolai Vasilyevich Gogol are explored through an overall examination and analysis of both the literary works and the literary styles found in them, as well as the literary text and its peculiarities. In addition, the historical period in which the writer wrote was also taken into account, primarily the literary trends such as critical realism and national romanticism and their influence on the literary style, including social influences from the spheres of religion, politics, ideology, and the dominant ideas, mindsets, and perceptions of the people in the then-Russian Empire.
Keywords: national romanticism; critical realism; folklore; Orthodoxy; Little Russia